We have the progression
91, 85, 79, ..., -29.
Also we can test:
85 - 91 = -6
79 - 85 = - 6
Hence, the progression is an arithmetic progression with d = -6.
Now, using the general formula of an arithmetic progression, we can find the position of term -29; as follows:
![\begin{gathered} a_n=a_1+(n-1)* d_{} \\ -29\text{ = 91 + (n - 1)(-6) } \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w1uliz5e7z3dhdalwqv4v89arrn5k49om6.png)
So n = 21
Now we know -29 is the term on the 21 position, we can proceed to find the sum of the first 21st terms of the progression:
![S_n\text{ = }(a_1+a_n)/(2)n\text{ }](https://img.qammunity.org/2023/formulas/mathematics/college/a39ex7zjlcxhpsv5v1xq1ziekrfiqjelyi.png)
Solving the formula we have:
![S_(21)\text{ = }\frac{91-29_{}}{2}\text{ x 21 }](https://img.qammunity.org/2023/formulas/mathematics/college/lqp2u8uzci0bevhwjdpnkp00we6v3puz90.png)
S₂₁ = 651